Bybanernes udvikling - Rallis, Tom (Proceedings from the Annual Transport Conference at Aalborg University, 1995)
Urban railways, Regional railways, Tramways are described according to opening year, size of town, length of lines and traffic as well as number of private cars for the period 1830 - 1995. In London lines opened 1835 - 53, when the city population increased from 3 mio. to 7 mio. (1850 - 1910), linelength today is approx. 3600 km and the number of railwaypass. has increased from 1150 to 1319 mio. against a total number of public transport pass. from 2350 - 2000 mio. but the number of cars has increased, in the period here described 1910 - 1990, from 0 to 400 cars per 1000 inh. Today Docklands Light Rail Transport is working. (LRT). In Tokyo they have reached 11.8 bio. railway pass. against 12 Bio. Public transport pass and 466 cars per 1000 inh. There are approx. 14 great cities (>10 mio. inh.) with urban railways, 63 other citites and 33 cities with LRT, all over the world. There has been a dilemma for every city, if they should invest in urban railways or urban motorways. In Europe there is only 1 km. urban motorway per 20.000 inh. against 3 km. in the USA. A great number of amr. towns has however opened urban railwys in the last 20 years, because of queueing problems on the urban motorways, high economic investments in urban motorways and environmental problems: accidents, noise and air pollution.